Digital design and optimization of higher order adaptive system using Continuous genetic algorithm - yadav, vijay; bhadauria, sarita singh (International Journal of Engineering and Technology, 2012)
An algorithm for design and optimization of higher order adaptive system are presented in this paper. In this work, the algorithm applied on the continuous search space parameter rather than discrete search space parameter. A new continuous genetic operator such that Rank based selection, Normal crossover and Mutations are used to improve the rate of convergence and solution quality has been proposed.